Relation between «rationality», self-esteem and school achievement in greek high school students - Στογιαννίδου Αριάδνη; Κιοσέογλου Γρηγόρης; Χατζηδημητριάδου Ελένη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF